(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
The early eighteenth century witnessed the early development of the dominant literary form of modern times, the novel. The novel emerged as a form with structure and interplay between individuals and their relationships to society. As a new form, the novel tends to make some significant, critical, and social statements about the society. Hence, the novel is used to create a new environment that is related to life and people. Indeed, this is what makes the novel appeal to readers as a new genre. Novelists either try to deal with daily social problems that happen in the lives of people or pretend that they are telling real stories. It is not surprising to find that Daniel Defoe molds his Robinson Crusoe (1719)on a real story while Samuel Richardson in Pamela (1740) turns out to be didactic to meet the needs of the growing numbers of female readers. On his part, Henry Fielding tries to expose his society to the readers in his masterpiece The History of Tom Jones, a Foundling (1749); from now on Tom Jones. Accordingly, the novel becomes popular at this time because it has something relevant to the mob; it deals with their social life, and they can identify themselves with its characters in the actual daily life. Through Tom Jones, Fielding presented “a true and realistic picture of human nature” (Kettle, 71). As long as its main concern is the existing society, novelists feel so involved that their criticism becomes direct, frank, and effective. My paper deals with these concerns as depicted in the novels mentioned above.